Prolonged mechanical ventilation after lung transplantation: risks factors and consequences on recipient outcome - Atchade, Enora; Boughaba, Aimane; Dinh, Alexy Tran; Jean-Baptiste, Sylvain; Tanaka, Sébastien; Copelovici, Léa; Lortat-Jacob, Brice; Roussel, Arnaud; Castier, Yves; Messika, Jonathan; Mal, Hervé; Tymowski, Christian de; et al. (Frontiers in Medicine, 2023)
BACKGROUND Risk factors and the incidence of prolonged mechanical ventilation (PMV) after lung transplantation (LT) have been poorly described. The study assessed predictive factors of PMV after LT. METHODS This observational, retrospective, monocentric study included all patients who received LT in Bichat Claude Bernard Hospital between January 2016 and December 2020. PMV was defined as a duration of MV > 14 days. Independent risk factors for PMV were studied using multivariate analysis. One-year survival depending on PMV was studied using Kaplan Meier and log-rank tests. A p value <0.05 was defined as significant. RESULTS 224 LT recipients were analysed. Sixty-four (28%) of them received PMV for a median duration of 34 [26-52] days versus 2 [1-3] days without PMV. Independent risk factors for PMV were higher body mass index (BMI) (p=0.031), diabetes mellitus of the recipient (p=0.039), ECMO support during surgery (p=0.029) and intraoperative transfusion > 5 red blood cell units (p<0.001). Increased mortality rates were observed at one year in recipients who received PMV (44% versus 15%, p<0.001). CONCLUSION PMV was associated with increased morbidity and mortality one year after LT. Preoperative risk factors (BMI and diabetes mellitus) must be considered when selecting and conditioning the recipients.